Fibroblasts Cultured on Nanowires Exhibit Low Motility, Impaired Cell Division, and DNA Damage. Issue 23 (27th June 2013) - Persson, Henrik; Købler, Carsten; Mølhave, Kristian; Samuelson, Lars; Tegenfeldt, Jonas O.; Oredsson, Stina; Prinz, Christelle N.
Abstract Nanowires are commonly used as tools for interfacing living cells, acting as biomolecule‐delivery vectors or electrodes. It is generally assumed that the small size of the nanowires ensures a minimal cellular perturbation, yet the effects of nanowires on cell migration and proliferation remain largely unknown. Fibroblast behaviour on vertical nanowire arrays is investigated, and it is shown that cell motility and proliferation rate are reduced on nanowires. Fibroblasts cultured on long nanowires exhibit failed cell division, DNA damage, increased ROS content and respiration. Using focused ion beam milling and scanning electron microscopy, highly curved but intact nuclear membranes are observed, showing no direct contact between the nanowires and the DNA. The nanowires possibly induce cellular stress and high respiration rates, which trigger the formation of ROS, which in turn results in DNA damage. These results are important guidelines to the design and interpretation of experiments involving nanowire‐based transfection and electrical characterization of living cells.